THE USE OF VIDEO CLASSES AS A LEARNING FACILITATING RESOURCE - Naiara Vicente de Góes, Ana; Phabryna de Mélo Oliveira Andrade, Karla; Nestor Felipe Gaudencio, Robson; Ferreira de Oliveira, Ribamar (Revista Gênero e Interdisciplinaridade, 2023)
This study intends to reflect on the relevance of using video lessons as a resource to facilitate learning, considering that these are widely used today. For the construction of the theoretical approach, studies by Moran (2002) and (2007), Oliveira and Júnior (2012), Ribeiro et.al (2016), Couto (2008), Mequelina (2008), Mendes (2010) are taken into account. ), Duso (2009) and Soares (2013), as well as considering the aspects proposed by the BNCC regarding this theme. To exemplify the importance of this didactic resource, ‘Telecurso’ and ‘Educa-PE’ are presented, which promote learning through video lessons. This research aims to point out the significance that video classes have, and, in this sense, it seeks to demonstrate that this resource is relevant to educational practice. Therefore, it is essential to know how to measure its applicability, that is, the teacher should not spend all of his class time just showing videos, but can use them as a complementary strategy in the learning of his students.